NEITHER BY FORCE, NOR BY REASON. THE FAILED ATTEMPT OF CHILE ’S NATIONAL STATE TO INCORPORATE THE MAPUCHE AND PEHUENCHE PEOPLES. (1810-1835) - Peralta Cabello, Paulina (Revista de Historia Social y de las Mentalidades, 2025)
This article analyzes the relations between  Chile’s recently established republican  State and the indigenous communities  then living south of the Bío Bío River.  More specifically, it identifies, since the  beginnings of the independence process,  but especially after the 1820’s, a will to  incorporate into the national project the  territories situated south of this frontier, as  well as their inhabitants. Among the legal  and political strategies displayed by the  ruling groups to materialize this purpose,  one can identify an early offer of Chilean  nationality, as well as a particular form of  citizenship defined by duties rather than  political rights. However, this strategy  could not be implemented because of  the stubborn resistance put up by most  indigenous communities with respect to  the new republican regime, whose alleged  benefits for themselves they failed to grasp.  It is likewise sustained that the natives’  resistance not only resulted in the failure  of that strategy, but also undermined the  “enlightened” and inclusive discourse  characteristic of the early decades, forcing  its replacement, starting in the mid-1830’s,  by a more exclusionary one, more interested  in territorial wealth than in the indigenous  inhabitants.
Keywords: Political Cityzenship; Etnical Relations; Chilean State (19th Century)